2006
DOI: 10.1007/s11524-006-9064-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Condom Use Intentions and Behaviors Among a Community-Based Sample of Latino Men in Los Angeles

Abstract: HIV/AIDS has disproportionately affected Latino communities. The majority of research addressing HIV risk behaviors within this population has focused on women. However, men who have sex with women (MSW) are a population increasingly becoming infected with HIV and heterosexual contact is the primary source of HIV transmission among Latinos diagnosed with AIDS. It has been assumed that because men are likely to control condom use, relationship factors are less likely to influence safer sex behavior among men. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
3
15
0
1
Order By: Relevance
“…In examining a wide range of individual, relationship, and contextual characteristics to better understand the determinants of condom use in this population, results indicated that the strongest barriers included men’s negative attitudes about condoms, their low self-efficacy for condom use, and not talking with their partner about condom use before having sex. These barriers have been highlighted as among the most important in the larger literature on heterosexual condom use based on relatively more advantaged samples [23, 44, 45] and are targeted in information-motivation-behavioral skills (IMB) approaches to HIV prevention [46]. Their relevance to condom use among homeless men is an important finding in that it suggests that the putative mechanisms of change targeted in most IMB-based interventions are also reasonable targets for interventions with homeless men.…”
Section: Discussionmentioning
confidence: 99%
“…In examining a wide range of individual, relationship, and contextual characteristics to better understand the determinants of condom use in this population, results indicated that the strongest barriers included men’s negative attitudes about condoms, their low self-efficacy for condom use, and not talking with their partner about condom use before having sex. These barriers have been highlighted as among the most important in the larger literature on heterosexual condom use based on relatively more advantaged samples [23, 44, 45] and are targeted in information-motivation-behavioral skills (IMB) approaches to HIV prevention [46]. Their relevance to condom use among homeless men is an important finding in that it suggests that the putative mechanisms of change targeted in most IMB-based interventions are also reasonable targets for interventions with homeless men.…”
Section: Discussionmentioning
confidence: 99%
“…Diaz (2000) suggested that although intentions for safer sex may exist, sociocultural factors, such as negative peer pressure, may disrupt intentions. Other studies suggest that non-MSM Latinos' behaviors are also influenced by their peers (Fasula & Miller, 2006;Harvey & Henderson, 2006;Marin, Gomez, Tschann, & Gregorich, 1997;Yan, Beck, Howard, Shattuck, & Kerr, 2008). For example, Yan et al (2008) found that among Latino youth, peer norms were directly related to alcohol use, and Marin et al (1997) found that heterosexual Latino men reported more condom use when they had strong condom social norms.…”
mentioning
confidence: 99%
“…Parece que la comunidad se acostumbró a las connotaciones de SIDA o VIH sin saber que todavía es una enfermedad latente y que no discrimina edad, sexo, raza o estatus económico. Según reportes de la CDC, en Estados Unidos la población que sobresale dentro de los nuevos infectados, es el hombre latino que tiene relaciones heterosexuales dentro de los 18 a 45 años, y esto está directamente relacionado con su negatividad de no usar preservativos (Harvey & Henderson, 2006;Knipper et al, 2007;De Santis, Valdés, Provencio-Vásquez & Gattamorta, 2015). Esta es una problemática que hay que abordar desde varios puntos de vista, empezando con la educación sexual en las aulas de clase.…”
Section: Epidemiología Actualunclassified